1998
DOI: 10.3109/03639049809085605
|View full text |Cite
|
Sign up to set email alerts
|

Gelation of Pluronic® F127-Polyethylene Glycol Mixtures: Relationship to PEG Molecular Weight

Abstract: The formation and melting of Pluronic F127 gels in the presence of polyethylene glycols (PEGs) has been studied. All the PEGs studied raised T1 and lowered T2 of 20% F127 gels; this effect was proportional to PEG concentration. At a certain critical "no-gel" concentration of PEG (Cng), F127 lost its ability to form gels. Cng was found to be inversely proportional to PEG molecular weight. An empirical relationship between Cng and PEG molecular weight was obtained which can be used to predict effects of PEGs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…In an attempt to solve these issues, we are reporting here an approach to finely tune P407 micelle interactions using poly­(ethylene glycol) (PEG400, M w = 400 g mol –1 ) (Figure A). This additive was previously used in P407 formulations to trigger the salting-out mechanism , but not as a yield stress regulator.…”
Section: Results and Discussionsupporting
confidence: 67%
“…In an attempt to solve these issues, we are reporting here an approach to finely tune P407 micelle interactions using poly­(ethylene glycol) (PEG400, M w = 400 g mol –1 ) (Figure A). This additive was previously used in P407 formulations to trigger the salting-out mechanism , but not as a yield stress regulator.…”
Section: Results and Discussionsupporting
confidence: 67%
“…Having higher values of viscoelastic moduli in the liquid state and lower gelation temperatures with increasing concentration of PEG 400, indicate possible hydrogen bonding between hydroxyl groups and ether groups among PEG 400 molecules or between PEG 400 and polyethylene groups in the Pluronics. Prior studies showed that the presence of short polyethylene glycol chains lowers the critical micellization temperature of Pluronic aqueous solutions 58,59 .
Fig. 5Effect of cosurfactant PEG 400 concentration on rheological properties and gelation temperature T gel .
…”
Section: Resultsmentioning
confidence: 97%
“…PEG has been reported in the literature to reduce G' with the increase of PEG concentration, 25 and that higher molecular weights of PEG disrupt gel formation at lower concentrations. 59 This has been attributed to entropic effects and increases in osmotic pressure disfavouring micelle formation, particularly for larger molecular weight polymers which are sterically excluded from the micelle. 60 For L-PAA G' has reduced in another study from 16 to 14 kPa when increasing concentration from 0.1 to 0.15 % w/w, respectively.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%